The Oil Price Shocks and GDP in Malaysia: Linear and Nonlinear Specification - Noor Aida, Noh (2011)
This study aimed to examine the effect of oil price shocks (world and domestic) on GDP in Malaysia from 1987 to 2009, using linear and nonlinear specification of oil price shocks. This study also examines the effect of world oil price on domestic petrol price. Results of the estimated multiple regression model indicates that the world oil price have significant impact on the Malaysia’s domestic petrol price. However, this impact is only partially. Obviously, it can be seen that either in the linear or nonlinear specification, the oil price shocks (domestic or world) do not have significant effects on GDP. It is only shocks on GDP will affect GDP itself. This implies that to increase GDP, innovation, technologies, and policies that able to increase productivities (which give a shock to GDP) will increase the GDP of Malaysia. Other policy implications and suggestions are also discussed.